With Terra Seismic earthquake prediction, we can be better prepared for earthquakes in Italy - Oleg Elshin (mediaGEO soc. coop., 2020)
Terra Seismic can predict most major earthquakes (M6.2 or greater) at least 2 - 5 months before they will strike.